Development of Mathematics Learning E-Modules with the PQ4R Strategy to Improve Students' Creative Thinking Abilities and Learning Independence - Pasaribu, Esra (FKIP Universitas Muhammadiyah Tangerang, 2024)
This research aims to analyze: 1) the validity, practicality and effectiveness of e-modules with the PQ4R strategy developed to increase students' creative thinking abilities and learning independence; 2) increasing students' creative thinking abilities through e-modules with the developed PQ4R strategy; 3) increasing students' learning independence through e-modules with the developed PQ4R strategy. This research is development research using the ADDIE development model. This development model consists of 5 development stages, namely Analyze, Define, Development, Implementation and Evaluation. From the results of trial I and trial II it was obtained: 1) E-module with the PQ4R strategy which was developed to increase students' creative thinking abilities and learning independence, has met the criteria of being valid, practical and effective; 2) Increasing the ability to think creatively using e-modules with the PQ4R strategy that has been developed as seen from the N-gain value in trial I of 0.36, increasing to 0.40 in trial II, meaning it is in the